Histomorphology of the gastrointestinal tract of domesticated Grasscutter (Thyronomys swinderianus) in Northern Nigeria - Obadiah, Byanet; PA, Abdu; A, Shekaro (Journal of Research in Biology, 2011)
The gastrointestinal tract was dissected from twelve matured domesticated grasscutters of both sexes. The stomach was J-shaped, simple monogastric relatively small in relation to the size of the animal. Its histological studies revealed three regions (cardiac, fundus and pylorus) with their gastric glands. Simple structure of the intestine; duodenum, jejunum and ileum and well developed large intestines; cecum, colon and rectum were also observed. Some common histological features of the intestine observed include: intestinal glands, the villi and goblet cells. The cecum with coma-shaped blind ended sac had three regions (base, body and apex) and Teniae with intervening haustra (sacculations) was the largest organ in the abdominal cavity and the largest segment of the intestine. The structure of the cecum suggests that it is the bacterial fermentation (digestion) vat, similar to that of the horse rumen in ruminant. The colon was the widest portion of the intestine and had fecal balls which were the indigestible portion of the fed that will pass through the rectum.